Sistem Pendukung Pengambilan Keputusan Penerimaan Beras Untuk Keluarga Miskin (Raskin) Di Kelurahan Sondakan Kecamatan Laweyan Kota Surakarta - Tri Irawati, Kusmiati, Wawan Laksito YS (Jurnal Ilmiah SINUS, 2013)
The purpose of submitting this research paper as a partial fulfillment of the requirements for gettingÂ  bachelor degree on the STMIK Sinar Nusantara, also aims to facilitate the process of determing the recipients raskin in the Sondakan. The method of collecting data used by the author in the preparation of this paper is an interview with the KASIÂ Â  of community development and feasibility assessment methods relatedÂ  to the recipient rice requirements raskin recipient. InÂ  theÂ  â€œDecision Support System Acceptance Raskinâ€ author providesÂ  a range calculationÂ  process based onÂ  the economic circumstances, the admissionsÂ  raskinÂ  processÂ  based onÂ  theÂ  range value. the results of this study stated that to get "Raskin" must meet 11 criteria set by the government. Â This system is made with the programming language Borland Delphi 7Â  and uses a MySQL database. Â  Keywords: Decision Support System Acceptance